Honeybees enhance quality litchi production - Kumar, Rajesh (Indian Horticulture, 2015)
Farmers should have the knowledge and skill of managing honey bee colonies in efficient manner. The strategic and planned honey bee management approaches like timely establishment of its strong colonies in sufficient number (6-8/ha) in litchi orchards. Above all, cordial/sweet relationship and collaboration between beekeepers and orchardists, would certainly lead to the enhancement of litchi fruit yield, quantitatively and qualitatively along with added advantage of economic and surplus production of litchi honey and other bee products. Consequently, this study provides the basis for continued improvement in context of specific pollination service value estimates.